To what extent do Bankers’ Compensation Packages induce risk taking behaviour? - Woolwright, Ryan (2011)
Bankers’ Compensation Schemes have long been a topic of interest for regulators and academics alike, with early seminal work on the links between pay and performance by Jensen and Meckling (1976), and early discussions around the impact of compensation on risk taking by Nalebuff and Stiglitz (1982). Despite interest saturating over time, the Financial Crisis of 2007/2008 catapulted Bankers’ Compensation Schemes back into the headlines of media and the forefront of politics. Much of the focus was generated due to the speculation that bankers’ compensation schemes were thought to allow and reward excessive risk taking behavior, which Jickling (2010) describes as one of the contributing factors to the Financial Crisis. Naturally a succession of reforms in the Financial Sector have been proposed aimed at averting future financial catastrophes. Notably, the Dodd Frank Review (2010) which forms part of what Obama describes as ‘the biggest reform of the Financial Sector since The Great Depression’. Part of the proposed reform has targeted bankers’ compensation schemes, from official reports such as the Dodd Frank review but also academic studies such as Bebchuk and Spamann (2009). Whilst the proposed reform responds logically to evidence on the risk-compensation relationship from studies such as Rajgopal and Shevlin (2002), the reforms fail to address the counter evidence and concerns. Such concerns are raised by numerous academics and financial commentators such as Carpenter and Walter (2010), Jensen and Murphy (1990), with particular reference to excessive shareholder risk taking and the composition of equity payments. The primary goal of this paper is to provide further more conclusive evidence on the extent to which current Bankers’ Compensation Schemes induce excessively risky strategies, whilst addressing some of the flaws in previous studies, detailed in the unique contributions of this paper. The findings will be of crucial importance as compensation reform will undoubtedly trouble the Financial Industry, so reform will need to have solid economic rationale, thus dismissing claims from the industry that it is a political knee jerk reaction to punish Bankers for the Crisis.